BODYGUARD is required for the biosynthesis of cutin in Arabidopsis. Issue 2 (15th March 2016) - Jakobson, Liina; Lindgren, Leif Ove; Verdier, Gaëtan; Laanemets, Kristiina; Brosché, Mikael; Beisson, Fred; Kollist, Hannes
Summary: The cuticle plays a critical role in plant survival during extreme drought conditions. There are, however, surprisingly, many gaps in our understanding of cuticle biosynthesis. An Arabidopsis thaliana T‐DNA mutant library was screened for mutants with enhanced transpiration using a simple condensation spot method. Five mutants, named cool breath ( cb ), were isolated. The cb5 mutant was found to be allelic to bodyguard ( bdg ), which is affected in an α/β‐hydrolase fold protein important for cuticle structure. The analysis of cuticle components in cb5 (renamed as bdg‐6 ) and another T‐DNA mutant allele ( bdg‐7 ) revealed no impairment in wax synthesis, but a strong decrease in total cutin monomer load in young leaves and flowers. Root suberin content was also reduced. Overexpression of BDG increased total leaf cutin monomer content nearly four times by affecting preferentially C18 polyunsaturated ω‐OH fatty acids and dicarboxylic acids. Whole‐plant gas exchange analysis showed that bdg‐6 had higher cuticular conductance and rate of transpiration; however, plant lines overexpressing BDG resembled the wild‐type with regard to these characteristics. This study identifies BDG as an important component of the cutin biosynthesis machinery in Arabidopsis. We also show that, using BDG, cutin can be greatly modified without altering the cuticular water barrier properties and transpiration.